HIV-1 Disease Progression and Drug Resistance Mutations among Children on First-Line Antiretroviral Therapy in Ethiopia - Yimam Getaneh; Fentabil Getnet; Feng Ning; Abdur Rashid; Lingjie Liao; Feng Yi; Yiming Shao (Biomedicines, 2023)
Background: High rates of disease progression and HIV drug resistance (HIVDR) among adults taking highly active antiretroviral treatment (HAART) in Sub-Saharan Africa were previously documented. However, children were generally not considered despite their greater risk. Hence, this study was aimed to evaluate HIV-1 disease progression and drug resistance mutation among children on first-line antiretroviral therapy in Ethiopia. Method: A longitudinal study was conducted among 551 HIV-positive children (<15 years old) recruited between 2017 and 2019 at 40 antiretroviral treatment delivery sites in Ethiopia. Disease progression was retrospectively measured over a 12-year (2007–2019) follow-up as the progress towards immunosuppression. Two consecutive viral load (VL) tests were conducted in 6-month intervals to assess virologic failure (VF). For children with VF, HIV-1 genotyping and sequencing was performed for the pol gene region using in-house assay validated at the Chinese Center for Disease Control and Prevention, and the Stanford HIVDB v9.0 algorithm was used for identification of drug resistance mutations. The Kaplan–Meier analysis and Cox proportional hazards regression model were used to estimate the rate and predictors of disease progression, respectively. Results: The disease progression rate was 6.3 per 100 person-years-observation (95% CI = 4.21–8.53). Overall immunosuppression (CD4 count < 200 cells/mm3) during the 12-year follow-up was 11.3% (95% CI = 7.5–15.1). Immunosuppression was significantly increased as of the mean duration of 10.5 (95% CI = 10.1–10.8) years (38.2%) to 67.8% at 12 years (p < 0.001). Overall, 14.5% had resistance to at least one drug, and 6.2% had multi-drug resistance. A resistance of 67.8% was observed among children with VF. Resistance to non-nucleotide reverse transcriptase inhibitors (NNRTI) and nucleotide reverse transcriptase inhibitors (NRTI) drugs were 11.4% and 10.1%, respectively. Mutations responsible for NRTI resistance were M184V (30.1%), K65R (12.1%), and D67N (5.6%). Moreover, NNRTI-associated mutations were K103N (14.8%), Y181C (11.8%), and G190A (7.7%). Children who had a history of opportunistic infection [AHR (95% CI) = 3.4 (1.8–6.2)], vitamin D < 20 ng/mL [AHR (95% CI) = 4.5 (2.1–9.9)], drug resistance [AHR (95% CI) = 2.2 (1.4–3.6)], and VF [AHR (95% CI) = 2.82 (1.21, 3.53)] had a higher hazard of disease progression; whereas, being orphan [AOR (95% CI) = 1.8 (1.2–3.1)], history of drug substitution [(AOR (95% CI) = 4.8 (2.1–6.5), hemoglobin < 12 mg/dL [AOR (95% CI) = 1.2 (1.1–2.1)] had higher odds of developing drug resistance. Conclusions: Immunosuppression was increasing over time and drug resistance was also substantially high. Enhancing routine monitoring of viral load and HIVDR and providing a vitamin-D supplement during clinical management could help improve the immunologic outcome. Limiting HAART substitution is also crucial for children taking HAART in Ethiopia.